2007
DOI: 10.1152/ajpgi.00295.2006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a protein hydrolysate responsive G protein-coupled receptor in enterocytes

Abstract: G protein-coupled receptors (GPCRs) have the potential to play a role as molecular sensors responsive to luminal dietary contents. Although such a role for GPCRs has been implicated in the intestinal response to protein hydrolysate, no GPCR directly involved in this process has been previously identified. In the present study, for the first time, we identified GPR93 expression in enterocytes and demonstrated its activation in these cells by protein hydrolysate with EC50 of 10.6 mg/ml as determined by the induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 66 publications
2
68
0
Order By: Relevance
“…Recent reports have shown that a G-protein coupled receptor (GPCR), GPR93, mediated the peptone-induced CCK secretion in STC-1 cells, 26,27) and we have demonstrated the involvement of the Gq pathway for BconP-induced CCK secretion in these cells. [28][29][30] We have recently found the calcium-sensing receptor, CaR, to function as the receptor for the arginine-rich 51-63 peptide in -conglycinin by inducing intracellular Ca 2þ mobilization for triggering subsequent CCK secretion in EECs.…”
Section: Discussionmentioning
confidence: 50%
“…Recent reports have shown that a G-protein coupled receptor (GPCR), GPR93, mediated the peptone-induced CCK secretion in STC-1 cells, 26,27) and we have demonstrated the involvement of the Gq pathway for BconP-induced CCK secretion in these cells. [28][29][30] We have recently found the calcium-sensing receptor, CaR, to function as the receptor for the arginine-rich 51-63 peptide in -conglycinin by inducing intracellular Ca 2þ mobilization for triggering subsequent CCK secretion in EECs.…”
Section: Discussionmentioning
confidence: 50%
“…The closest structurally related GPCRs to LPA5 are P2Y5 and P2Y9, which are also activated by LPA (16,46). However, we found that only LPA5 is activated by partially digested dietary protein (peptone).…”
mentioning
confidence: 61%
“…The mitochondria-targeted aequorin (mtAEQ) and LPA5 expression vectors were constructed as previously described (16). The vector base for the reporter constructs, pBVluc, was a generous gift from Dr. Bert Vogelstein (The Johns Hopkins Kimmel Cancer Center).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations